German-Ukrainian business relationships: Trust development in the face of institutional uncertainty and cultural differences - Guido Möllering; Florian Stache (Max Planck Institute for the Study of Societies, 2007)
The paper examines cultural differences and institutional uncertainty as important factors in the development of trust as a basis for successful international business relationships. The authors focus their investigation on the potential that actors have in becoming aware of and creatively responding to institutional contexts, cultural differences and the challenge of trust development. Empirically, the authors look at German-Ukrainian business relationships and draw on a qualitative analysis of field interviews conducted at the time of the so-called "Orange Revolution". They conclude overall that the trust dilemma in international business relationships can be overcome through reflexivity and creativity, and they give many practical examples of what this means.
Keywords: 300; Auslandsgeschäft; Internationale Wirtschaftsbeziehungen; Vertrauen; Kulturpsychologie; Institutionelle Infrastruktur; Ukraine; Deutschland